Examen especial a la cuenta de ingresos y gastos del gobierno autónomo descentralizado parroquial rural Panguintza, cantón Centinela del Cóndor de la provincia de Zamora Chinchipe, en el periodo 2014 - Narváez Narváez, Celia María (2016)
This research was conducted in order to apply tests and special examination techniques in the Parish Government Panguitza to obtain evidence to support the final report to determine the degree of strength and reasonableness of account balances under consideration. The project objectives were successfully met, when analyzing the budget items, an average level of confidence found 50% revenue growth and 60% expenses; to raise the standards to be followed for the correction of the shortcomings Control Regulations Nos raised: 405-02 Organization government accounting system; 405-04 Supporting documentation and archiving; 405-05 "Opportunity record of economic events and financial reporting"; 405-06 Reconciliation of account balances; 405-07 Forms and documents; Hiring 406-03; finally it fulfilled 100% the surrender of the special examination report to the accounts Income and Expenditure Parish Government "Nangaritza" the President, detallándole the conclusions and recommendations of each finding. This research used the scientific, deductive, inductive and analytical methods for developing techniques direct observation survey and interviews with the secretary bookkeeper and president of GAD Parish Panguintza applied, allowing develop the special examination from planning to the communication of results, internal control and evaluation, among other materials that allowed the development of fieldwork. The results of the investigation, the main reportable conditions encountered by evidence presented by Secretary Treasurer of the Vestry are related to the wrong registration of transactions, poor bank reconciliations, lack of supporting documentation fully legalized, 5 supporting documentation and file, among others; situation leads to make some recommendations as meeting the standards of accounting control in the institution for a veracity of the information required, in addition to design and implement a general internal rules applicable and controlled in the GAD Parish Rural Panguintza, in order to obtain improved profitability in its activities and improve the administrative and financial management.